2022
DOI: 10.1021/acs.est.2c00381
|View full text |Cite
|
Sign up to set email alerts
|

Emerging and Legacy Per- and Polyfluoroalkyl Substances in an Elderly Population in Jinan, China: The Exposure Level, Short-Term Variation, and Intake Assessment

Abstract: Human exposure to per- and polyfluoroalkyl substances (PFASs) has gained worldwide attention due to their widespread presence in the environment and adverse health effects, but the exposure assessment in the elderly is still lacking. This study aimed to assess exposures to 3 emerging PFASs (chlorinated polyfluoroalkyl ether sulfonic acids, Cl-PFESAs) and 15 legacy PFASs. The temporal variability of internal exposures and intake amounts of these PFASs were evaluated among a population of 76 healthy elderly adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Dietary exposure due to food and drink uptake was considered the dominant pathway of exposure followed by inhalation of house dust and dermal absorption. PFOA was the predominant PFAS in the blood of adults, making the largest contribution to the estimated total daily intake of PFAS . The estimated median intake of PFOA was 1.46 ng/kg-bw/day, according to an exposure assessment survey conducted through a dietary questionnaire among a population of 76 healthy elderly adults aged from 60 to 69 in Jinan, China over 5 consecutive months . Accordingly, the exposure doses of PFOA from the use of sanitary pads, panty liners, menstrual cups, and paper diapers estimated in the study were calculated to have proportions of 3.2, 0.6, 52.7, and 84.2% of the intake dose, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary exposure due to food and drink uptake was considered the dominant pathway of exposure followed by inhalation of house dust and dermal absorption. PFOA was the predominant PFAS in the blood of adults, making the largest contribution to the estimated total daily intake of PFAS . The estimated median intake of PFOA was 1.46 ng/kg-bw/day, according to an exposure assessment survey conducted through a dietary questionnaire among a population of 76 healthy elderly adults aged from 60 to 69 in Jinan, China over 5 consecutive months . Accordingly, the exposure doses of PFOA from the use of sanitary pads, panty liners, menstrual cups, and paper diapers estimated in the study were calculated to have proportions of 3.2, 0.6, 52.7, and 84.2% of the intake dose, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Sample processing, quality control and data extraction, metabolite identification, data curation, data quantification, and data normalization were conducted according to previously published protocols. 40 In brief, the samples were precipitated with methanol for 2 min under severe vibration (GenoGrinder 2000), and then the metabolites were extracted by centrifugation. The supernatant was then separated into five fractions: Two fractions were analyzed by two different reverse phase/ultra-performance liquid chromatography–mass spectrum (RP/UPLC-MS/MS) methods using positive ion mode electrospray ionization (ESI).…”
Section: Methodsmentioning
confidence: 99%
“…Reports from around the world indicate that PFAS are widely present in various food matrices, especially in animal-derived foods (e.g., dairy products, eggs, aquatic food, and meat). Many studies have found a strong positive correlation between fish consumption and human internal PFAS exposure levels. , According to the Sixth Chinese Total Diet Study, the estimated weekly intake (EWI) of PFOS, PFOA, and 6:2 Cl-PFESA in the Chinese population was 2.17, 2.72, and 2.75 ng/kg body weight (bw) per week, respectively. These levels already exceeded the guideline proposed by the European Food Safety Authority in 2020, which is 4.4 ng/kg bw per week for the sum of PFOA, PFOS, perfluorononanoic acid (PFNA), and PFHxS .…”
Section: Introductionmentioning
confidence: 99%